Influence of Occupational Health and Safety System Implementation on Occupational Diseases to Factory Workers - Arys Hasta Baruna; Indasah (Journal for Quality in Public Health, 2022)
Occupational health and safety system (OHS) is expected to prevent occupational diseases, incidents during work, and to guarantee the protection of workers. They should integrate the OHS system in its management. As a result, there is a feasibility of minimizing occupational diseases in factory workers because of the efficiency protection from the OHS division. The study used a literature review that aims to identify the implementation of OHS system and to lessen ocupational diseases on factory workers. The utilized database programs were Google Scholar, PubMed, Science Direct, and PEDro using the keywords Ergonomic, OHS, and occupational diseases. There were found 10 articles related to the topic that was published from 2019 to 2021. Six of them were from Indonesia’s journal while the rest were from international journal.Many big factories had already applied the OHS system in Indonesia to ensure the safety of their workers whereas the OHS meeting was less important to be discussed in Sweden.There was a particular disease that could not be avoided such as hearing disorders due to the continuously high-intensity noise exposure. However, OHS system had succeed to measure the danger level of an activity at work and minimize the casualties.